2010
DOI: 10.1111/j.1365-2311.2010.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of thermal tolerance contributes to the invasion potential of Mediterranean fruit flies (Ceratitis capitata)

Abstract: Abstract. 1. The invasion success of Ceratitis capitata probably stems from physiological, morphological, and behavioural adaptations that enable them to survive in different habitats. However, it is generally poorly understood if variation in acute thermal tolerance and its phenotypic plasticity might be important in facilitating survival of C. capitata upon introduction to novel environments.2. Here, by comparison of widely distributed C. capitata with a narrowly distributed congener, C. rosa, we show that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
113
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 59 publications
10
113
0
Order By: Relevance
“…Each value corresponds to the mean of three replicates (±S.E.M., 5 flies per replicate). Statistics: a two-way ANOVA was carried out for each sex, body part and gene; ⁄ p < 0.05, ⁄⁄ p < 0.01. multiple introductions that allowed maintenance of genetic variability, the wide variety of host plants (Liquido et al, 1991), and variation in physiological tolerance to climatic stress (Nyamukondiwa et al, 2010). The presence of C. capitata in areas with subfreezing temperatures during winter has been suggested to be a consequence of migration from nearby temperature-favorable areas at the beginning of the summer, rather than overwintering of pre-imagos or adults (Israely et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each value corresponds to the mean of three replicates (±S.E.M., 5 flies per replicate). Statistics: a two-way ANOVA was carried out for each sex, body part and gene; ⁄ p < 0.05, ⁄⁄ p < 0.01. multiple introductions that allowed maintenance of genetic variability, the wide variety of host plants (Liquido et al, 1991), and variation in physiological tolerance to climatic stress (Nyamukondiwa et al, 2010). The presence of C. capitata in areas with subfreezing temperatures during winter has been suggested to be a consequence of migration from nearby temperature-favorable areas at the beginning of the summer, rather than overwintering of pre-imagos or adults (Israely et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the factors that determine its distribution and abundance and, in this regard, the ability of C. capitata to adjust to temperature variations has been recently investigated, showing a broad thermal tolerance (Nyamukondiwa and Terblanche, 2009;Nyamukondiwa et al, 2010;Weldon et al, 2011;Basson et al, 2012). Basson et al (2012) demonstrated that cold exposure reduced C. capitata survival, which suggests the possibility of a chill-dependent injury, although flies showed no metabolic or fecundity costs.…”
Section: Introductionmentioning
confidence: 99%
“…This framework has been developed for a more mechanistic understanding of plant invasions but has, to our knowledge, never been applied to invasive animals. Generally, most evidence for phenotypic plasticity as an important trait of invasive organisms is derived from plants [15][16][17][18][19] with some studies also investigating vertebrates [20], aquatic organisms [7,[21][22][23][24][25][26][27], entognatha [28,29] or insects [8,30,31]. Evidence from terrestrial molluscs, however, is largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread invasive species often are successful across a range of habitat temperatures and thus offer a special opportunity for analysis of differences in acclimatization potential and genetic variation due to thermal selection (Chown et al, 2007;Sorte et al, 2010b;Lockwood and Somero, 2011). An ability to acclimatize to new conditions has long been suggested as an important factor in determining invasion success (Yeh and Price, 2004;Smith, 2009;Nyamukondiwa et al, 2010). Additionally, invasive species, Master of all trades: thermal acclimation and adaptation of cardiac function in a broadly distributed marine invasive species, the European green crab, Carcinus maenas Carolyn K. Tepolt* and George N. Somero especially those with short generation times and high levels of genetic variation, may have the ability to adapt rapidly to their new environments, as has been shown for Drosophila subobscura across multiple thermal clines in its non-native range (Balanyá et al, 2006).…”
Section: Introductionmentioning
confidence: 99%